FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - Alfinjo, Harris Wijaya; Vivianti, Jenny (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study is to obtain empirical evidence about the influence of variable current ratio, debt to equity ratio, return on assets, total assets turnover, return on equity, and firm size on firm value. The object sample of this research are non-financial companies listed in Indonesia Stock Exchange (IDX) period 2019 to 2021 using the purposive sampling method and the sampling resulted in 204 companies with 612 data. This research analysis used multiple regression analysis method. The results of this study indicate that variable return on assets, return on equity, and firm size have an effect on firm value. While variable current ratio, debt to equity ratio and total assets turnover have no effect on firm value.